Diferencias en la propiedad planta y equipo y propiedades de inversión bajo normas internacionales de información financiera completas y PYMES - Romero Rivera, Roberto Carlos (2015)
This paper primarily aims to implement the accounting treatment of property, plant and equipment, allowing companies to submit financial information of high quality, understandable and comparable and enforceable under the International Financial Reporting Standards. Property, plant and equipment are all acquired, built or under construction, with the intention to employ them permanently, for the production or supply of other goods and services, for rental or for use in the administration, tangible assets They are not intended for sale and whose useful life exceeds the year of use. Account of property, plant and equipment, is considered permanent capital investment that companies make in accordance with their solvency and operations capacity. For the development of the research was done using methods and research techniques that helped make the work better because it brought together relevant and necessary information that contributed to the development work. The proposal was specified as is described, whose main objective is to conduct a study of investment in property, plant and equipment and its impact on business assets. Structural components and detailed examples were carried out in addition to describing the implementation phase and logistical resources. Finally the assessment of the feasibility of the proposal was made, and analysis both in the different technical, economic, social and environmental dimensions.